Mode of Delivery according to Leisure Time Physical Activity before and during Pregnancy: A Multicenter Cohort Study of Low-Risk Women - Emilie Nor Nielsen; Per Kragh Andersen; Hanne Kristine Hegaard; Mette Juhl (Hindawi Limited, 2017)
Objectives. To examine the association between maternal leisure time physical activity and mode of delivery. Study Design. Population-based multicentre cohort. From the Danish Dystocia Study, we included 2,435 nulliparous women, who delivered a singleton infant in cephalic presentation at term after spontaneous onset of labor in 2004-2005. We analysed mode of delivery according to self-reported physical activity at four stages, that is, the year before pregnancy and during first, second, and third trimester, in logistic regression models. Further, we combined physical activity measures at all four stages in one variable for a proportional odds model for cumulative logits. Main Outcome Measures. Mode of delivery (emergency caesarean section; vacuum extractor; spontaneous vaginal delivery). Results. The odds of emergency caesarean section decreased with increasing levels of physical activity with statistically significant trends at all four time stages except the third trimester. This tendency was confirmed in the proportional odds model showing 28% higher odds of a more complicated mode of delivery among women with a low activity level compared to moderately active women. Conclusions. We found increasing leisure time physical activity before and during pregnancy associated with a less complicated delivery among low-risk, nulliparous women.